Prevalence of institutional delivery and associated factors in Dodota Woreda (district), Oromia regional state, Ethiopia - Fikre Addis Alem; Demissie Meaza (BMC, 2012)
Abstract Background Giving birth in a medical institution under the care and supervision of trained health-care providers promotes child survival and reduces the risk of maternal mortality. According to Ethiopian Demographic and Health Survey (EDHS) 2005 and 2011, the proportion of women utilizing safe delivery service in the country in general and in Oromia region in particular is very low. About 30% of the eligible mothers received Ante Natal Care (ANC) service and only 8% of the mothers sought care for delivery in the region. The aim of this study is to determine the prevalence of institutional delivery and understand the factors associated with institutional delivery in Dodota, Woreda, Oromia Region. Methods A community based cross sectional study that employed both quantitative and a supplementary qualitative method was conducted from Jan 10-30, 2011 in Dodota Woreda. Multi stage sampling method was used in selection of study participants and total of 506 women who gave birth in the last two years were interviewed. Qualitative data was collected through focus group discussions (FGDs). Data was entered and analyzed using EPI info 3.5.1 and SPSS version 16.0. Frequencies, binary and multiple logistic regression analysis were done, OR and 95% confidence interval were calculated. Results Only 18.2% of the mothers gave birth to their last baby in health facilities. Urban residence, educational level of mothers, pregnancy related health problems, previous history of prolonged labour, and decision made by husbands or relatives showed significant positive association with utilization of institutional delivery services (P < 0.05). While ANC attendance during the index pregnancy did not show any association. Conclusion Institutional Delivery is low. Increasing accessibility of the delivery services and educating husbands not only mothers appear very important factors in improving institutional delivery. Health education on the importance of institutional delivery should also address the general population. The quality and content of the ANC services need to be investigated.